2019
DOI: 10.1080/14786419.2019.1663516
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and hemostatic effects of Linaria reflexa Desf

Abstract: The work presented here was aimed to investigate the in vivo anti-inflammatory and in vitro hemostatic activities of Linaria reflexa extract and to establish the relationship between its bioactivity and chemical composition. Twenty-three secondary metabolites were identified, most of them are good anti-inflammatory agents, in line with data by carrageenin-induced rat paw edema assays of the n-butanol extract showing high anti-inflammatory inhibition (63.90%) of edema swelling in the rat paw at the dose 200 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…They explained that the decreased blood clotting time against AgNPs can be due to phytochemical of A. wilhelmsii extract as capping agents in the surface of biosynthesized AgNPs and also, negative charges of these NPs 87 . According to a previous report, the presence of high amount of flavonoid glycosides in the extract of some medicinal plants causes a potent hemostatic effect 88 . It has been reported that various species of the genus Centaurea have high amounts of flavonoids.…”
Section: Resultsmentioning
confidence: 99%
“…They explained that the decreased blood clotting time against AgNPs can be due to phytochemical of A. wilhelmsii extract as capping agents in the surface of biosynthesized AgNPs and also, negative charges of these NPs 87 . According to a previous report, the presence of high amount of flavonoid glycosides in the extract of some medicinal plants causes a potent hemostatic effect 88 . It has been reported that various species of the genus Centaurea have high amounts of flavonoids.…”
Section: Resultsmentioning
confidence: 99%
“…The potential of red algae ethanol extract as an anti-inflammatory agent for periodontitis has been widely studied [ [105] , [106] , [107] ]. However, the anti-inflammatory activity of Gracilaria textorii ethanol extract (GTEE) has not yet been reported.…”
Section: Resultsmentioning
confidence: 99%